Influence of two ovulation-inducing agents on the pituitary response and follicle blood flow in mares - Boakari, Y. L. [UNESP]; Ferreira, J. C.; Canesin, H. S. [UNESP]; Thompson, D. L.; Lima, F. S.; Pantoja, J. C.F. [UNESP]; Meira, C. [UNESP] (Elsevier, 2017)
The objective of the current study was to evaluate the effects of deslorelin and hCG, two ovulation-inducing therapies, on LH surge and follicle vascularity in mares. Thirty mares were either treated with 1.5 mg IM of deslorelin, 2,500 IU IV of hCG or 2 mL IM of NaCl 0.9% (GnRH, hCG and Saline groups, respectively). Power-flow Doppler examination and blood collection were performed every hour during the first 12 hours after treatment (H0) and every six hours between hours 12 (H12) and 30 (H30) after treatment. Moreover, endpoints were evaluated every hour through the last six hours before ovulation (OV-6 to OV-1). In GnRH group, plasma LH concentration progressively increased (P < 0.001) during the first 6 hours after treatment and remained high (P > 0.1) until OV-1. A significant increase in LH concentrations was first detected (P < 0.05) at 24 hours after treatment in hCG group, while no changes (P > 0.1) on LH levels were found during H0-H30 and between OV-6 and OV-1 in the Saline group. Independent of the treatment, significant variations on the percentage of the follicle wall with Doppler signals were not observed (P > 0.1) throughout the entire experiment. A weak correlation between the preovulatory follicle vascularity and the plasma LH concentration was found in GnRH, hCG and Saline groups (r = +0.29, +0.29 and −0.23, respectively; P ˂ 0.0001). These results described for the first time the immediate and continuous pituitary response to ovulation-inducing therapy with injectable deslorelin. Moreover, spontaneous and induced ovulations were not preceded by an increased follicle vascularity, which differs from previous reports in large animals.
Keywords: Deslorelin; Doppler ultrasonography; Follicle vascularity; hCG; LH